De novo stop‐lost germline mutation in FGFR3 causes severe chondrodysplasia in the progeny of a Holstein bull. (2nd April 2020) - Häfliger, I. M.; Letko, A.; Murgiano, L.; Drögemüller, C.
Summary: Fifteen cases of chondrodysplasia characterized by disproportionate dwarfism occurred in the progeny of a single Holstein bull. A de novo mutation event in the germline of the sire was suspected as cause. Whole‐genome sequencing revealed a single protein‐changing variant in the stop codon of FGFR3 gene on chromosome 6. Sanger sequencing of EDTA blood proved that this variant occurred de novo and segregates perfectly with the observed phenotype in the affected cattle family. FGFR3 is an important regulator gene in bone formation owing to its key role in the bone elongation induced by FGFR3‐dimers. The detected paternally inherited stop‐lost variant in FGFR3 is predicted to add 93 additional amino acids to the protein's C‐terminus. This study provides a second example of a dominant FGFR3 stop‐lost variant as a pathogenic mutation of a severe form of chondrodysplasia. Even though FGFR3 is known to be associated with dwarfism and growth disorders in human and sheep, this study is the first to describe FGFR3 ‐associated chondrodysplasia in cattle.